Clinical efficacy of autogenous dentin grafts with guided bone regeneration for horizontal ridge augmentation: a prospective observational study. Issue 6 (June 2022) - Wang, W.; Jiang, Y.; Wang, D.; Mei, D.; Xu, H.; Zhao, B.
Abstract: The aim of this study was to evaluate the efficacy of autogenous dentin grafts with guided bone regeneration (GBR) for horizontal ridge augmentation. Nineteen patients with dentition and bone defects in whom tooth/teeth extraction was indicated were recruited. Autogenous teeth were prepared, fixed on the buccal sides of the defects, and covered with bone powder and resorbable membranes before implantation. The horizontal bone mass at 0 mm (W1), 3 mm (W2), and 6 mm (W3) from the alveolar crest was recorded using cone beam computed tomography, before, immediately after, and 6 months after dentin grafting. All adverse effects were recorded. The implant stability quotient (ISQ) was measured 6 months after implantation. Twenty-eight implants were placed 6 months after dentin grafting. At this time point, the bone mass was 4.72 ± 0.72 mm (W1), 7.35 ± 1.57 mm (W2), and 8.96 ± 2.38 mm (W3), which was significantly different from that before the surgery ( P  < 0.05). The bone gain was 2.50 ± 0.72 mm (W1), 4.10 ± 1.42 mm (W2), and 4.56 ± 2.09 mm (W3). No soft tissue dehiscence or infection was observed. Overall, 26.3% of the patients experienced severe pain after dentin grafting. The ISQ was 78.31 ± 6.64 at 6 months after implantation. Autogenous tooth roots with GBR might be effective for horizontal ridge augmentation. This technique could be an alternative to augmentation using autogenous bone grafts.